Capaian Hasil Inovasi Produk dan Digital Marketing Usaha Rengginang di Rowoindah – Jember - Putri Fitria Soleha; Agus Supriono (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The Covid-19 pandemic that has entered Indonesia has had a negative impact on the community's economic sector. The economic sectors affected by this pandemic are generally small and medium-sized businesses that have experienced a decline in sales turnover. In an effort to deal with and survive in the Covid-19 pandemic situation, business actors are required to innovate and be creative in selling their business products. The rengginang business actor in Rowoindah village, Jember is one of the businesses affected by Covid-19 and has experienced a decline in sales turnover. Therefore, in this activity, assistance will be provided to help Rengginang business actors survive and develop through product innovation training into various flavors and sales through digital marketing. After the activity was carried out, the Rengginang business actors felt a positive impact for their future business development.